2008
DOI: 10.1523/jneurosci.1134-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Foxg1Is Required for Development of the Vertebrate Olfactory System

Abstract: Illuminating the molecular identity and regulation of early progenitor cells in the olfactory sensory epithelium represents an important challenge in the field of neural development. We show in both mouse and zebrafish that the winged helix transcription factor Foxg1 is expressed in an early progenitor population of the olfactory placode. In the mouse, Foxg1 is first expressed throughout the olfactory placode but later becomes restricted to the ventrolateral olfactory epithelium. The essential role of Foxg1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 60 publications
3
102
0
Order By: Relevance
“…3). Recent studies in the zebrafish, in which morpholino oligonucleotides were used to reduce Foxg1 levels in a mosaic fashion (Duggan et al, 2008), also showed that Foxg1 influences OE neurogenesis in a cellautonomous fashion, a result opposite to what would have been expected if Foxg1 acts by controlling the expression of a secreted growth factor, such as an FGF.…”
Section: Foxg1 Activity Supports a Self-sustaining Neurogenic Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…3). Recent studies in the zebrafish, in which morpholino oligonucleotides were used to reduce Foxg1 levels in a mosaic fashion (Duggan et al, 2008), also showed that Foxg1 influences OE neurogenesis in a cellautonomous fashion, a result opposite to what would have been expected if Foxg1 acts by controlling the expression of a secreted growth factor, such as an FGF.…”
Section: Foxg1 Activity Supports a Self-sustaining Neurogenic Networkmentioning
confidence: 99%
“…Foxg1 cre/+ mice, in which the Foxg1 coding sequence is replaced by the gene encoding Cre-recombinase (Cre) (Hebert and McConnell, 2000), were maintained on an outbred Swiss Webster background (Harlan, Indianapolis, IN, USA). Although expression of Cre recombinase in the Foxg1 locus has been shown to have some effects on telencephalon development when the allele is maintained on a congenic C57bl/6 background (Eagleson et al, 2007), when maintained on an outbred background, Foxg1 cre/cre mice have been shown to have nervous system phenotypes identical to those observed in another Foxg1 null strain, Foxg1 lacZ/lacZ (Duggan et al, 2008;Eagleson et al, 2007;Hanashima et al, 2007;Martynoga et al, 2005;Muzio and Mallamaci, 2005;Pratt et al, 2004 …”
Section: Gdf11mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the current model suggests that progenitor cells expressing Ascl1 gives rise to intermediate precursors that require Neurog1 for differentiation (Cau et al, 2002;Cau et al, 1997;Guillemot et al, 1993;Nicolay et al, 2006). More recently, it has been shown that the wingedhelix transcription factor Foxg1 acts upstream of Ascl1 for correct olfactory neurogenesis (Duggan et al, 2008). Similarly, microRNAs of the miR-200 family have been implicated in the maintenance of olfactory neurogenesis (Choi et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…As for correct placode formation at earlier stages, the Cxcl12a-Cxcr4b interaction is required for the proper guidance of pioneer axons (Miyasaka et al, 2007;Yoshihara, 2009); the Robo2 receptor and Slit ligands have also been implicated in fasciculation and guidance of axons of olfactory neurons Yoshihara, 2009). Surprisingly, however, although a requirement for Foxg1 and microRNAs has apparently been conserved between zebrafish and mouse during the early steps of olfactory neurogenesis, nothing is known concerning proneural gene function during the development of either early or late-born olfactory neurons in zebrafish (Choi et al, 2008;Duggan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%